Interplay of protein primary sequence, lipid membrane, and chaperone in β‐barrel assembly. (16th January 2021) - Tiwari, Pankaj B.; Mahalakshmi, Radhakrishnan
Abstract: The outer membrane of a Gram‐negative bacterium is a crucial barrier between the external environment and its internal physiology. This barrier is bridged selectively by β‐barrel outer membrane proteins (OMPs). The in vivo folding and biogenesis of OMPs necessitates the assistance of the outer membrane chaperone BamA. Nevertheless, OMPs retain the ability of independent self‐assembly in vitro . Hence, it is unclear whether substrate–chaperone dynamics is influenced by the intrinsic ability of OMPs to fold, the magnitude of BamA–OMP interdependence, and the contribution of BamA to the kinetics of OMP assembly. We addressed this by monitoring the assembly kinetics of multiple 8‐stranded β‐barrel OMP substrates with(out) BamA. We also examined whether BamA is species‐specific, or nonspecifically accelerates folding kinetics of substrates from independent species. Our findings reveal BamA as a substrate‐independent promiscuous molecular chaperone, which assists the unfolded OMP to overcome the kinetic barrier imposed by the bilayer membrane. We additionally show that while BamA kinetically accelerates OMP folding, the OMP primary sequence remains a vital deciding element in its assembly rate. Our study provides unexpected insights on OMP assembly and the functional relevance of BamA in vivo .